REFORMA AGRARIA: MEMBANGUN ULANG RELASI NEGARA DAN MASYARAKAT ADAT MELALUI PENGAKUAN DAN PERLINDUNGAN MASYARAKAT ADAT - JT Pareke (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2020)
Abstract: This study aims to describe the efforts to reestablish the relations between the State and indigenous peoples in the protection of indigenous peoples. The benefits of this study are expected to be used by interested parties to formulate policy options in the protection of indigenous peoples through the establishment of Regional Regulations. This study uses a combination of empirical and normative juridical approaches. An empirical juridical approach is an approach used to view social phenomena related to law and its practice. Normative juridical approach is an approach that uses secondary data in the form of primary, secondary and tertiary legal materials. The results of this study show that: First, As long as there are no laws that specifically regulate indigenous peoples, the regulation of indigenous peoples through Government Regulations and Regional Regulations can be justified to fill the legal vacuum to ensure fair legal certainty; Second, the legal product of Lebong Regency Regional Regulation No. 4 of 2017 concerning to Recognition and Protection of Rejang Indigenous Peoples in Lebong Regency, and Rejang Lebong Regency Regional Regulation No. 5 of 2018 concerning to Recognition and Protection of Indigenous Peoples in Rejang Lebong Regency is a role model of how local government efforts in reestablish state and indigenous peoples relations to solve structural agrarian problems by recognizing territories along with traditional rights of Rejang indigenous peoples through legal politics of recognition and the protection of indigenous peoples by establishing regional regulations. Keywords: Agrarian Reform; Relations; State; Indigenous People;